Transport current density at temperatures up to 25 K of Cu/Ag composite sheathed 122-type tapes and wires. (2nd October 2017) - Liu, Shifa; Lin, Kaili; Yao, Chao; Zhang, Xianping; Dong, Chiheng; Wang, Dongliang; Awaji, Satoshi; Kumakura, Hiroaki; Ma, Yanwei
Abstract: The fabrication of iron-based superconductors with high transport critical current density ( J c ) and low cost is a crucial determinant of whether they can be used for practical applications. In this paper, Cu/Ag composite sheathed Sr0.6 K0.4 Fe2 As2 (Sr122) tapes and Ba0.6 K0.4 Fe2 As2 (Ba122) round wires were fabricated via an ex situ powder-in-tube method and heat-treated by the hot pressing and hot isostatic pressing process respectively. In order to thoroughly reveal the application potential of Cu/Ag composite sheathed '122' iron pnictide superconductors, transport J c of tapes and wires in high fields at temperatures up to 25 K was measured. High transport J c of 4.4 × 10 4 A cm −2 at 4.2 K and 3.6 × 10 3 A cm −2 at 20 K in 10 T was achieved in Cu/Ag composite sheathed Sr122 tapes. Transport J c of Ba122 wires is 9.4 × 10 3 A cm −2 at 4.2 K and 1.9 × 10 3 A cm −2 at 20 K in 10 T. These results demonstrate the great potential of Cu/Ag composite sheathed '122' iron pnictide superconducting tapes and wires for high-field applications at intermediate temperatures around 20 K, which can be easily obtained by using cryocoolers.